2021
DOI: 10.3390/diagnostics11020277
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-11 PET/CT Follow-Up of Patients with Prostate Cancer with Bone Metastases Who Had Reduced Bone Density after Androgen Deprivation Therapy

Abstract: Bone metastases from prostate cancer (PCa) often show an increase in density on computed tomography (CT) after successful androgen deprivation therapy (ADT). Density may be reduced, however, as the disease progresses or, contrarily, when disease is no longer active. The current study investigated the role of 68Ga-PSMA-11 positron emission tomography/computed tomography (PET/CT) in differentiating between these two conditions. Methods: The study cohort included 15 PCa patients with sclerotic/blastic bone metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Unlike our results, they observed a significant correlation with PSA trends, likely due to their access to detailed patient data throughout the therapy . This indicates the relevance of PSMA-PET for response assessment, which seems to be effective also in early stages of prostate cancer not only to localize disease, but also to assess the patient's risk 25 , 26 . In this regard, PSMA-PET appears to be well-suited for assessing response to systemic non-RLT therapies, including chemotherapy and hormone therapy 27 - 29 .…”
Section: Discussionmentioning
confidence: 86%
“…Unlike our results, they observed a significant correlation with PSA trends, likely due to their access to detailed patient data throughout the therapy . This indicates the relevance of PSMA-PET for response assessment, which seems to be effective also in early stages of prostate cancer not only to localize disease, but also to assess the patient's risk 25 , 26 . In this regard, PSMA-PET appears to be well-suited for assessing response to systemic non-RLT therapies, including chemotherapy and hormone therapy 27 - 29 .…”
Section: Discussionmentioning
confidence: 86%
“…Similar to how an increase in the density of sclerotic bone metastases can be associated with either a therapeutic response or progression, studies in prostate cancer under androgen deprivation therapy have found that a decrease in the density of initially sclerotic bone metastases and a reduction in the uptake of bone-targeting agents can also be indicative of both scenarios (Figure 1) (38,39). This may be attributed to the suppression of the osteoblastic effect of testosterone in the event of a therapeutic response or the progression towards predominant lytic phenomena following the acquisition of resistance to hormonal therapy (38). In prostate cancer, this limitation could be overcome by the advent of radiolabeled PSMA PET/CT.…”
Section: Decreasing Density Of Bone Metastasesmentioning
confidence: 89%
“…In a retrospective analysis involving prostate cancer patients receiving androgen deprivation therapy, findings revealed that among the 65 patients with bone metastases who underwent 68 Ga-PSMA PET/CT scans, 15 individuals (23%) displayed a decrease in the density of their bone metastases. Among the 37 lesions that exhibited reduced density, 21 (57%) were negative on PET scans, while 16 (43%) had intense 68 Ga-PSMA uptake ( 38 ). Significantly, PET scans did not detect any positive findings in the bone lesions of patients who exhibited a treatment response.…”
Section: Bone Scan: the Historical Cornerstone In The Management Of B...mentioning
confidence: 99%
“…The present issue of the International Journal of Molecular Sciences ( IJMS ) includes publications on staging using PSMA PET for the initial management of patients with prostate cancer [ 11 ] and on restaging using PSMA PET/CT for patients with prostate cancer at PSA relapse [ 12 , 13 , 14 , 15 ]. Other publications report the impact of the chemical structure of small inhibitory molecules for the PSMA receptor [ 16 ], animal models of PSMA and prostate cancer [ 17 ], and associations between the androgen receptor signal transduction pathway and the expression of PSMA [ 18 , 19 , 20 ].…”
mentioning
confidence: 99%